Method for analyzing students’ utilization of prior physics learning in new contexts - McBride, Dyan L.; Zollman, Dean A.; Rebello, N. Sanjay (My University, 2010)
In prior research, the classification of concepts into three types—descriptive, hypothetical and theoretical—has allowed for the association of students’ use of different concept types with their level of understanding. Previous studies have also examined the ways in which students link concepts to determine whether students have a meaningful understanding of principles of evolution. In this study, we build on our previous work that seeks to examine how students use prior knowledge in new situations and context, as well as present an adaptation of concept and concept-link categorization previously used in biology education research. In this adaptation, concepts are categorized on the basis of the observability of the concept exemplars and are shown to be dependent upon the knowledge level of the student. We use this categorization method to examine how students use prior knowledge when presented with an opportunity to apply physics in a new context, namely, wavefront aberrometry. Results indicate that students primarily utilize lower-level concepts, which is in agreement with previous research findings. We also found that students are able to create links between different levels of concepts, and that the type of links created can give insight to how deeply they understood the physics of the new context.
Keywords: Adaptation of concept; Concept-link categorization; Prior knowledge